Algorithms for estimating the main reliability parameters of low-voltage equipment of shop-floor network schemes - R. M. Petrova; E. I. Gracheva (Омский научный вестник)
The article presents the classification of fuses, breakers, circuit breakers and packet switches. The laws of change of probabilistic reliability characteristics of the studied devices, as well as low-voltage cable lines are determined. Types of functions of change of basic reliability parameters are determined and corresponding graphical dependences are shown. The comparison of the obtained results of the values of probability of failure-free operation time with the requirements of GOST and passport data is carried out. The investigated probabilistic parameters of lowvoltage devices and cable lines are checked for compliance with the accepted law of distribution of random variables.